2014
DOI: 10.1179/1743284713y.0000000462
|View full text |Cite
|
Sign up to set email alerts
|

Development of γ-fibre recrystallisation texture in medium–chromium ferritic stainless steels

Abstract: The texture development and c-fibre recrystallisation texture formation mechanism of ferritic stainless steels under different rolling processes were investigated. It was shown that the surface texture development was absolutely different from the centre texture development. In conventional rolled band, strong a-fibre was formed at the centre layer and it was weakened after hot band annealing; after cold rolling, the centre texture was characterised by sharp a-fibre and weak c-fibre with a peak at {111},110., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…21 In conclusion, a strong intensity of {114}〈110〉, which is between {001}〈110〉 and {112}〈110〉, was formed. That is also in good agreement with the crystal rotation path {001} 〈110〉 → {114}〈110〉 → {112}〈110〉 which is mentioned by Gao et al 22…”
Section: Discussionsupporting
confidence: 90%
“…21 In conclusion, a strong intensity of {114}〈110〉, which is between {001}〈110〉 and {112}〈110〉, was formed. That is also in good agreement with the crystal rotation path {001} 〈110〉 → {114}〈110〉 → {112}〈110〉 which is mentioned by Gao et al 22…”
Section: Discussionsupporting
confidence: 90%
“…The formation of the recrystallization texture depends on the initial deformation texture 15 . As mentioned above, {111} 〈112〉 recrystallized grains nucleate in {111}〈110〉 recovery grains or vice-versa 10 . In the present study, it was observed that the {111}〈110〉 component was more intense after direct rolling than with an intermediate annealing for 80% cold rolling (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Yazawa et al 11 reported that the r ̅ value is related to the γ-fiber in the recrystallization texture. Furthermore, the enhancement and uniformity of the γ-fiber is essential in order to improve the r ̅ value [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation